Pyroelectric Energy Conversion and Its ApplicationsFlexible Energy Harvesters and Sensors - Thakre, Atul; Kumar, Ajeet; Song, Hyun-Cheol; Jeong, Dae-Yong; Ryu, Jungho (MDPI, 2019)
Among the various forms of natural energies, heat is the most prevalent and least harvested energy. Scavenging and detecting stray thermal energy for conversion into electrical energy can provide a cost-effective and reliable energy source for modern electrical appliances and sensor applications. Along with this, flexible devices have attracted considerable attention in scientific and industrial communities as wearable and implantable harvesters in addition to traditional thermal sensor applications. This review mainly discusses thermal energy conversion through pyroelectric phenomena in various lead-free as well as lead-based ceramics and polymers for flexible pyroelectric energy harvesting and sensor applications. The corresponding thermodynamic heat cycles and figures of merit of the pyroelectric materials for energy harvesting and heat sensing applications are also briefly discussed. Moreover, this study provides guidance on designing pyroelectric materials for flexible pyroelectric and hybrid energy harvesting.
Keywords: FREE PIEZOELECTRIC MATERIALS; ELECTRICAL ENERGY; THERMAL-ENERGY; WASTE HEAT; FERROELECTRIC PROPERTIES; THICK-FILM; LARGE-AREA; NANOGENERATOR; GENERATOR; PERFORMANCE